The Shifting Shades of Elegance on Display in 1930S Estoril: When Tourism Meets Fashion - Carvalho, Cristina (2015)
In 1914 Fausto Figueiredo, the mastermind behind Estoril’s resort, wrote the town resembled a woman whose staggering beauty only lacked the artificial sense of fashion trends, in order to drive men wild. As his project developed across a valley by the sea, facilities and events created for tourist enjoyment and based on cosmopolitan aesthetic principles internationally conveyed the image the new resort sought for itself. In the 1930s Estoril’s shopping arcades sold the latest fashion items recently arrived from Paris, while stores in Lisbon advertised specific clothing pieces meant to be worn while playing golf or enjoying equestrian shows. The Modas & Bordados magazine also taught beauty tips to middle and upper-class women, besides publishing models to be worn at the Casino, at the Tamariz beach, and on posh racing events. On the other hand, the Casino’s advertisements often entitled its programmes (whether dinners, balls, theme parties, or teas) as elegant initiatives. The venue served also as the perfect set for hair styling competitions, conferences on cosmetics, and fashion shows later mocked at radio appearances and newspapers. A satirical play then performed at a folk theatre even revolved around the hedonism copied after Paris and the Riviera, and one of the scenes focused on an indescribable modern beverage: the Cocktail. The 1930s also set the tone for a new type of skin beauty: out with the pale and on with the tan. Movie stars were the role models to emulate, and in 1935 British actress Heather Thatcher’s funny episode in Estoril proved there was more to tanning than just lying under the sun. This empirical paper is based on the research the author has conducted for her Ph.D thesis entitled Tourism in the Estoril-Cascais Coastal Axis (1929–1939): Equipments, Events and Destination Promotion.